Current trends in reconfigurable modular robots design. (8th June 2017) - Brunete, Alberto; Ranganath, Avinash; Segovia, Sergio; de Frutos, Javier Perez; Hernando, Miguel; Gambao, Ernesto
This article presents a review on trends in modular reconfigurable robots, comparing the evolution of the features of the most significant robots over the years and focusing on the latest designs. These features are reconfiguration, docking, degrees of freedom, locomotion, control, communications, size, and powering. For each feature, some of the most relevant designs are presented and the current trends in the design are discussed.